Natural Light Intensity Model of Surat Thani Province - Pradip na talang, Tada; Rakthai, Saksri (Journal of Vocational Education in Agriculture, 2022)
The objective of this research was to create a natural light intensity model of Surat Thani Province for designing natural light intensity control technology for agriculture or other work related to natural light. The structures of the natural environment influencing natural light intensity were studied. A local meteorological data collection station was installed at Surat Thani College of Agriculture and Technology (8°52'42"N, 98°49'30"E). The station recorded 5 real-time data, (1) natural light intensity (2) air temperature (3) relative humidity (4) wind speed and (5) wind direction. The data were analysed using correlation analysis and multiple regression analysis. The data analysis of the relationship between variables and interests was based on data transformations using natural logarithm values. The natural light intensity model was created in the form of a Linear Regression with Natural Logarithm Transformation Model or LRNLT-Model, and then the performance of the model created was tested using data from the meteorological data collection station. It was found that the natural light intensity values calculated from the model was consistent with the actual measurement values. The difference in the data in the form of values indicating the discrepancy between the calculated values from the model and the actual measurement values (RMSD) was 8.18 percent. The data bias was directed towards the measurement values and it was only 0.23% more than the calculated values (MBD).